A predictive model of interfacial interactions between functionalised carbon fibre surfaces cross-linked with epoxy resin. (3rd May 2018) - Demir, Baris; Beggs, Kathleen M.; Fox, Bronwyn L.; Servinis, Linden; Henderson, Luke C.; Walsh, Tiffany R.
Abstract: Attachment of amine-bearing molecules, denoted surface grafted molecules (SGMs), onto the surface of carbon fibre has been previously shown to enhance interfacial interactions at the carbon fibre/epoxy interface. However, the design principles inherent to optimising this enhancement are not yet established. Here, we investigate the influence of SGM design criteria on the interfacial mechanical response for three types of SGM via predictions based on molecular dynamics simulations, and by experimental measurements. The SGMs are covalently grafted to the graphitic fibre surface via in situ generated and decomposed phenyl diazo salts. All three SGMs possess a phenyl ring as the surface attachment point, and differ by the number and/or position ( meta or para ) of the amine-terminated side-chain(s) attached to the ring. The single-chain meta -substituted SGM produces the least interfacial enhancement, while the double-chain meta -substituted SGM enhances the interfacial shear strength by 29% relative to the control. In contrast, the single-chain para -SGM performs almost comparably to the double-chain meta -SGM. Our modelling predictions recover this trend and offer molecular-scale explanations for these findings, providing guidance in the design of effective surface-tailoring strategies to realise enhancements in the shear response of carbon fibre–epoxy interfaces.